Current molecular methods for the detection of hepatitis B virus quasispecies. (9th August 2016) - Rybicka, Magda; Stalke, Piotr; Bielawski, Krzysztof Piotr
Summary: Chronic HBV infection affects more than 240 million people worldwide and is associated with a broad range of clinical manifestations including liver cirrhosis, liver failure and hepatocellular carcinoma. Because of the lack of an efficient cure for chronic hepatitis B, the main goal of antiviral therapy is the prevention of liver disease progression coupled with prolonged survival of patients. Because HBV viral load has been shown to be a crucial determinant of the progression of liver damage, these goals can be achieved as long as HBV replication can be suppressed. Unfortunately, long‐term therapy with the low‐to‐moderate genetic barrier drugs, which are still recommended in a majority of developing countries, are strongly associated with HBV resistance development and treatment failure. In such cases, the precise and accurate determination of drug‐resistant variants in an individual patient before treatment is important for a proper choice of first‐line potent therapy. Nowadays, a number of techniques are available to study HBV quasispecies evolution. This review describes the advantages and limitations of various assays detecting drug‐resistant HBV variants. Copyright © 2016 John Wiley & Sons, Ltd.